The prevalence of Corynosoma parasite worms in the great cormorants and the Baltic herring in the northern Baltic Sea, Finland - Sahlstén Johannes; Rajasilta Marjut; Mäkinen Katja; Hänninen Jari (Elsevier, 2025)
During 2014–2019, the prevalence of Corynosoma spp., a parasite species in great cormorants (Phalacrocorax carbo spp.) and in Baltic herring (Clupea harengus membras), was studied in the Archipelago and the Bothnian Seas of the northern Baltic Sea. These results suggest that cormorants may act as a definitive host for these acanthocephalan parasites. Adults were more infected with the parasites than juveniles, which could be due to their larger size. A lower prevalence of Corynosoma spp. in juveniles may be because smaller cormorants eat smaller fish that have less parasites. We found that the most abundant corynosoma species in both the Baltic herring and cormorants were Corynosoma semerme, whereas only a few individuals of C. strumosum and only one C. magdaleni were found. The prevalence of corynosoma in herring increased from 2014 to 2018, and individuals in the Bothnian Sea were infected less frequently than herring in the Archipelago Sea. Results also showed that infected herring individuals were generally larger than non-infected individuals, which could be explained by their size and their feeding habits. Currently, the changing environment of the Baltic Sea may cause an effect on the herring making them more susceptible to infections. Our results, therefore, emphasize the importance of the regular monitoring of infections and the parasite-host relationships in the Baltic Sea.